Fluent in English with Social Media Platforms during the Covid-19 Pandemic - Carla Maretha; Gali Alrajafi (Universitas Lancang Kuning, 2022)
This study is conducted to provide a very enjoyable teaching reference in order to improve English learning outcomes, especially in the speaking skills of English Department students at Universitas Muhammadiyah Lampung. The purpose of this study is to provide a fun learning solution through the social media platform Instagram so that students can be motivated to continue to carry out distance learning during the COVID-19 pandemic so that there is an increase in learning outcomes to speak. This study puts forward a quantitative approach using the Quasi Experimental design method. The steps taken include: 1) giving a pre-test several times; 2) provide treatment; 3) give a pot-test several times. This research shows that Instagram can be an effective speaking learning media. This is evidenced by the acceptance of Ha in this study. Learning English during the pandemic is indeed a challenge for teachers and students. The boredom of studying at home is one of the causes of decreased learning achievement. The use of social media can be a solution to this problem. Instagram can be used as a fun learning medium (Fidian, 2017). Instagram provides learning motivation for students (Rohim, 2020). By using this social media, students' desire to learn increases. They can play while doing the teaching and learning process, especially learning English.